Cycles of the Housing Market in Hungary from the Economic Crisis until Today - Harnos, László (Naše gospodarstvo/Our economy, 2018)
The main aim of this paper is to identify the underlying reasons for the cyclical nature of the Hungarian housing market, in particular the business cycles, the construction, and market participants’ expectations. Our research was conducted based on analysis of statistical data and of the housing market indices. As a result, it can be stated that cyclic behaviour of the housing market may be explained primarily with business cycles, but state subsidies and mortgages also affect the variations. Accordingly, the increasing lending and the high amount of subsidies can generate a price bubble. The supply of second-hand dwellings looks more flexible compared with that of new ones. However, the expectations of market operators do not have a demonstrable effect on the housing market.